Resonance assignment of coiled-coil 3 (CC3) domain of human STIM1 - Gupta, Agrim; Kitzler, Christian Manuel; Rathner, Petr; Fahrner, Marc; Grabmayr, Herwig; Rathner, Adriana; Romanin, Christoph; Müller, Norbert (Biomolecular NMR assignments, 2021)
The protein stromal interaction molecule 1 (STIM1) plays a pivotal role in mediating store-operated calcium entry (SOCE) into cells, which is essential for adaptive immunity. It acts as a calcium sensor in the endoplasmic reticulum (ER) and extends into the cytosol, where it changes from an inactive (tight) to an active (extended) oligomeric form upon calcium store depletion. NMR studies of this protein are challenging due to its membrane-spanning and aggregation properties. Therefore follow the divide-and-conquer approach, focusing on individual domains first is in order. The cytosolic part is predicted to have a large content of coiled-coil (CC) structure. We report the 1H, 13C, 15N chemical shift assignments of the CC3 domain. This domain is crucial for the stabilisation of the tight quiescent form of STIM1 as well as for activating the ORAI calcium channel by direct contact, in the extended active form.
Keywords: Stromal Interaction Molecule 1; Neoplasm Proteins; sekvence aminokyselin; Store-operated calcium entry; Humans; proteinové domény; lidé; protein STIM1; Nuclear Magnetic Resonance, Biomolecular; Coiled-coil structure; CRAC; nukleární magnetická rezonance biomolekulární; Calcium channel; Amino Acid Sequence; Protein Domains; nádorové proteiny